2017
DOI: 10.7759/cureus.1529
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleukemiosis: Two Case Reports

Abstract: Extramedullary tumors composed of myeloblasts or monoblasts can present in various locations. Patients with a history of acute myeloid leukemia (AML) can present with neuropathic pain and no evidence of relapse of their leukemia. Neuroleukemiosis is a form of extramedullary tumor present in the peripheral nervous systems (PNS) of leukemia patients. We report two AML patients who were in remission and later presented with neurological symptoms due to neuroleukemiosis with negative bone marrow biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…However, it was not associated with EMR, suggesting that the GVL effect did not extend to the extramedullary sites [3]. Previous case reports of EMR in the brachial plexus revealed that GVHD occurred before or after the relapse [8][9][10]. Our patient had concurrent development of cGVHD and EMR in the brachial plexus.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…However, it was not associated with EMR, suggesting that the GVL effect did not extend to the extramedullary sites [3]. Previous case reports of EMR in the brachial plexus revealed that GVHD occurred before or after the relapse [8][9][10]. Our patient had concurrent development of cGVHD and EMR in the brachial plexus.…”
Section: Discussionmentioning
confidence: 44%
“…Three cases of EMR in the brachial plexus without HSCT were diagnosed clinically due to systemic relapse [5][6][7]. In addition, three previous case reports involved cases of EMR in the brachial plexus in patients with AML who underwent HSCT [8,9]. Two of these cases were definitively diagnosed via biopsy and successfully treated with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroleukemiosis is a very rare complication of leukemia. Until now, only 15 cases have been reported ( Table 1 ) [ 1 12 ]. Including the case described in this report, the mean age of patients was 40.2 years, and four patients were aged < 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Intractable neuropathic pain, numbness, and weakness can be the first signs of neuroleukemiosis. With only neuropathic symptoms present, it is easy to misdiagnose a leukemic mass infiltrating the peripheral nervous system, especially if the blood smear and bone marrow biopsy are negative for leukemia [ 12 ]. Differential diagnosis for neuroleukemiosis include Guillain-Barre syndrome, neurotoxicity from chemotherapy and abscess [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its diagnosis is sometimes delayed because neurological symptoms often occur during the remission phase, and nonspecific symptoms such as paresthesias in AML patients are sometimes considered to indicate neurotoxicity from chemotherapy. 2,3,[5][6][7] Nerve biopsy is a gold standard for the diagnosis of neuroleukemiosis, but it is not recommended if there is a concern that this may result in neurological deficit. 1 As with our patient, the clinical features, imaging findings, and treatment response support the diagnosis of neuroleukemiosis when nerve biopsy is not possible.…”
mentioning
confidence: 99%